Parachartergus fraternus (Gribodo) (Hymenoptera: Vespidae: Polistinae) Uses Venom When Taking Caterpillar Prey - Eric J. Olson (Psyche: A Journal of Entomology)
A forager of the eusocial wasp Parachartergus fraternus used its venom to subdue an unidentified small caterpillar, and another P. fraternus forager repeatedly stung a large saturniid caterpillar. In both instances, the wasp stung the larva and then waited nearby until the prey was fully paralyzed before biting it into manageable packets of meat. A review of the literature on social wasp foraging yielded no similar observations of a social wasp using venom when killing prey. Elements of the foraging behavior of P. fraternus are also seen in the foraging behavior of the Eumeninae, the solitary wasp taxon most closely related to eusocial wasps.